KARAKTERISTIK DAN ANALISIS PROFIL ASAM LEMAK MINYAK IKAN KOMERSIAL (Softgel) IMPOR DI WILAYAH KALIMANTAN UTARA - Bija, Stephanie; Murniati, Murniati (Bajang Institute, 2024)
Fish oil content Omega-3 fatty acid which playes an important roles in health and food field. The quality of imported fish oil (softgel) needs to be considered, so it remains safe and beneficial for the society. This research aims to analyze the characteristics and fatty acid profile of imported commercial fish oil (softgel) that available in the North Kalimantan. Analysis of the fatty acid profile used the 18-6-1/MU/SMM-SIG (GC-FID) method. This method uses the Gas Chromatography-Flame Ionization Detector (GC-FID) technique. Commercial fish oil (softgel) samples are coded A and the fatty acid profile is described, including saturated fatty acids (SFA), monounsaturated fatty acids (MUFA), and compound unsaturated fatty acids (PUFA). The results show that imported fish oil (softgel) had a golden yellow color, no fishy odor, and contained SFA 50.48%, MUFA 25.44%, and PUFA 12.65%. Omega-3 fatty acid is 5.34%.